Opportunities and barriers to achieve GHG emissions reduction targets set under the Paris Agreement and potential contribution to the SDGs in seven LAC countries - CGIAR Research Program on Climate Change, Agriculture and Food Security (2020)
An inclusive approach to re-imagine how the academic, research, business and public policy sectors can support and incentivize the changes needed to raise the level of ambition and achieve SDG